Study on oviposition attractants to Aedes albopictus - DENG Tian-fu; MO Jian-chu; CHENG Jia-an (浙江大学学报. 农业与生命科学版)
To develop novel techniques for mosquito monitoring, the attractive effects of 5 dyes (methylene blue, brilliant blue, carmine, fruit green, and tartrazine) and 10 compounds (acetic acid, propionic acid, heptanoic acid, caproic acid, ethyl acetate, ethyl butanoate, dimethyl disulfide, ammonia, L-lactic acid and 1-octen-3-ol) on the gravid Aedes albopictus females were determined in laboratory and under hemi-field condition. The results indicate that Ae. albopictus laid significantly more eggs in the solution of methylene blue, brilliant blue or carmine than in the distilled water without any dyes. Among the 10 compounds tested, the eggs laid by Ae. albopictus in the acetic acid (0.001 mg· L-1), propionic acid (0.01 mg·L-1), ethyl acetate (0.01 mg·L-1), and 1-octen-3-ol (0.01-1 mg·L-1) water solution were significantly more than that in the distilled water. The hemi-field tests indicated that, when dye was mixed with compound solution at the laboratory effective concentration, it showed greater attractive effects than the compound on the oviposition of Ae. albopictus. This means that the compounds maybe need higher concentration to attract Ae. albopictus females in the field.